Disabled students' entrepreneurial action: The role of religious beliefs - Dakung Reuel Johnmark; Tsenba Wummen Soemunti; Orobia Laura; John C. Munene; Waswa Balunywa (Cogent Business & Management, 2016)
People world over are engaged in entrepreneurship activities to promote societal and economic advancement. Along with the growing importance of entrepreneurial activity in economic growth comes concern over the religious dimension, especially as it relates to the Christian and Muslim world views. Religious beliefs are seen to be important in triggering entrepreneurial action. This study focuses on investigating the predicting role of religious beliefs on entrepreneurial action of disabled students. The study followed a descriptive survey where quantitative approach was employed. A total number of 262 questionnaires was administered to disabled students across the tertiary institutions (Universities, Polytechnics and Colleges) in Plateau State and Abuja-Nigeria. Analysis of data involved the use of descriptive statistics, correlation and Structural Equation Model. All the formulated hypotheses were also tested and the results revealed that vocation, social service and social networks significantly and positively influence entrepreneurial action. Like any other research, this study is limited in the following ways. Since only a single research methodological approach was employed, future research could undertake a mixed approach and triangulate to validate the current findings. Further, a longitudinal approach should be employed to study entrepreneurial action trends among disabled students over years. Finally, religious beliefs was studied and based on the results, there are other factors that may contribute in explaining entrepreneurial action of disabled students that were not part of this study.
Keywords: 650